Visualizing History: Narrative and Discourse Analysis of Historical Dioramas at Museum Sejarah Nasional Indonesia - Dery Saefudin; Mulyadi; Siti Nurani (English Language Education Department, Universitas Majalengka, 2025)
Museums are not only places to display historical objects, but also powerful spaces that shape how people understand the past through stories, language, and images. This study explores how ideological messages are built through written texts and visual elements in the dioramas of the National Museum of Indonesian History. Using a qualitative approach, the research combines narrative analysis based on Tzvetan Todorov’s five narrative stages and Stuart Hall’s theory of representation. Data were collected through observation and photo documentation of 51 dioramas across four main historical periods. The findings show that the museum presents Indonesian history in a clear but state-centered way, emphasizing national pride, anti-colonial struggle, and male heroism. The texts often use nationalistic and elite-centered language, promoting a single dominant view of history. This excludes other voices, such as those of women, local communities, and ordinary people. The study shows that museums do more than inform. They help shape public understanding of history. Therefore, it is important to examine museum language critically to promote a more inclusive national narrative.